PENGARUH DISTRIBUSI FISIK TERHADAP PENJUALAN PUPUK NPK MEREK MAHKOTA (STUDI KASUS: PT. SENTANA ADIDAYA PRATAMA) - Kiki Fotedi Pramono (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2016)
The pattern of this policy requires the placement of inventory at each location, and placement of such supplies require a good handling so that supplies can be optimal, meaning that it can meet the demands of existing demand without storage is too great which causes buildup in the warehouse which resulted in high cost savings and possibilities the greater the damage to the product. PT. Sentana Superpower Pratama (PT. SADP) is engaged in the domestic Agrochemical, with products such as fertilizers and pesticides. Products PT. SADP 90% is aimed at consumers of the companies of oil palm plantations. With a distribution system that exists today in the PT. SADP frequent delays in product availability branch warehouse, so sending fertilizer to customers late and cause complaints and claims from customers. The purpose of this paper is to analyze the influence of distribution channels and physical distribution which consists of processing reservations, inventory control, handling of goods, warehousing and transportation of the Crown brand NPK fertilizer sales at PT. SADP. In this study, the population in question are all customers of PT. SADP status is still actively buying NPK fertilizer from time to time, these customers consist of oil palm plantation companies large and small plantations, its number is 985 customers. Methods to determine samples with Isaac formula and Michael with a sample of 212 samples. The results of writing is: independent variable that is processing the booking (X1), inventory control (X2), handling of goods (X3), warehousing (X4), and transport (X5) simultaneously have a positive and significant impact on the dependent variable, namely the sale of NPK brand crown in PT. SADP. Partial testing of mind that the inventory control, ordering processing, handling of goods and transport significantly influence brand NPK fertilizer sales crown,and warehousing no significant effect on the brand NPK fertilizer sales crown.Keywords: Distribusi Fisik dan Penjualan Pupuk NPK.